FluCare: Results from a Randomised Feasibility Study of a Complex Intervention to Increase Care Home Staff Influenza Vaccination Rates - Wright, David; Patel, Amrish; Blacklock, Jeanette; Bion, Veronica; Birt, Linda; Bryant, Terry; Clark, Allan; Cook, Luke; Griffiths, Alys; Guillard, Cecile; et al. (Archives of Clinical and Biomedical Research, 2024)
Background: To protect care home residents, annual staff influenza vaccination uptake is recommended to be greater than 75%. In the UK it is under 40%. With barriers and enablers to care home staff flu vaccine uptake identified, the purpose of this study was to feasibility test a theory informed intervention to improve vaccination rates. Methods: This was a five-arm (one intervention, four different control) study designed to inform the development of a definitive trial protocol. The intervention comprised of videos/posters to change vaccination attitudes, on-site clinics to increase access, a financial incentive for homes to reach target, and monthly monitoring of vaccination uptake. Control arms consisted of a mix of monthly or end of the study monitoring and provision of informational materials to identify the most suitable control arm for a definitive trial. Care homes were recruited via sector associations and purposively allocated. The feasibility outcomes were: ability to recruit enough homes; data quality (variables reported, variable completeness and consistency with a national reporting system); intervention implementation; control arm reactivity bias and signal of efficacy. Staff vaccination data was collated from homes and via a national healthcare tracking system. Process evaluation and economic data collation were undertaken to optimise intervention and research design. Results: Ten homes were recruited as per target within 11 weeks. Recruitment delays meant intervention delivery began towards end of flu season. Only 2 clinics took place in each home. All homes in intervention and chosen control arm (monthly monitoring only) reported all variables with over 90% completeness. There was a 15% difference between control homes’ reported vaccination rates and that in the national healthcare tracker, home reported data was more reliable. Signal of efficacy: intervention arm had a vaccination rate 13.6% higher than control arm. Bias: control arm did not have a higher vaccination rate than usual care control. Conclusions: Better recruitment processes, earlier start in flu season, and data collection direct from care homes are required for a definitive trial. A control arm of monthly monitoring only was identified as optimal for data collection purposes and minimising reactivity bias. The signal of efficacy was acceptable.